Epigenetic Regulation (Including Micro-RNAs, DNA Methylation and Histone Modifications) of Rheumatoid Arthritis: A Systematic Review - Melissa Payet (MDPI AG, 2021)
The inflammatory reaction in rheumatoid arthritis (RA) is controlled by major epigenetic modifications that modulate the phenotype of synovial and immune cells. The aim of this work was to perform a systematic review focusing on miR expression, DNA methylation and histone modifications in RA. We demonstrated that, in human samples, the expressions of miR-155, miR-146a and miR-150 were significantly decreased while the expression of miR-410-3p was significantly increased in the RA group. Moreover, miR-146a significantly decreased pro-autoimmune IL-17 cytokine expression in RA. In a murine model, miR-34a inhibition can ameliorate the arthritis score. However, this evidence remain critically insufficient to support current therapeutic applications in RA patients.